COMPARISON OF ETOMIDATE AND PROPOFOL AS INDUCTION AGENTS IN MODIFIED ELECTROCONVULSIVE THERAPY - SHARMA, TEJASVINI; MAKKER, ROBINA; RANJAN, PRITISH; KYIZOM, TENZIN; GARG, SHOBIT (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to compare the effects of induction agents Propofol and Etomidate on hemodynamic parameters (Heart rate, Systolic Blood Pressure, Diastolic Blood pressure, and mean arterial pressure) in modified electroconvulsive therapy (ECT). Methods: It was a prospective, randomized, and double-blinded study. The present study was conducted in the Department of Anaesthesiology at our tertiary care multispeciality referral hospital, Shri Guru Ram Rai Institute of Medical and Health Sciences, Patel Nagar, Dehradun. A total of 80 adult patients in the age group 20–50 years belonging to American Society of Anesthesiologists physical status I and II were included in the study. They were randomly allocated to Group I (Propofol) and Group II (Etomidate), with 40 patients in each group. The duration of the study was September 2018–February 2020. Results: Both Etomidate and Propofol have been proposed as good induction agents to be used for ECT, but each has its own merits and demerits. Propofol leads to a significantly shorter seizure duration as compared to Etomidate. Propofol has the advantage of having rapid and smooth recovery as compared to Etomidate. Recovery criteria in terms of return to spontaneous respiration, consciousness, and fully responding were statistically significant between the two drug groups (p<0.001). Conclusion: Propofol has the advantage of having rapid and smooth recovery as compared to Etomidate. Minimum side effects were seen in both groups. Subseizure was seen with the Propofol group more than Etomidate. Hence, we conclude that Etomidate is a better induction agent as compared to Propofol in modified ECT.